Soil fertility norms for Sathgudi sweet orange (Citrus sinensis) - LAKSHM, L MUKUNDA; RAMANA, K T VENKATA; PATIL, PRAKASH; SRIVASTAVA, A K (The Indian Journal of Agricultural Sciences, 2017)
Soil fertility norms for citrus cultivars are limited. An extensive survey was carried out in ninety five-bearing orchards of Sathgudi sweet orange (Citrus sinensis Osbeck) in YSR Kadapa, Nalgonda, Nellore and Anantapur districts of Andhra Pradesh to develop soil fertility norms through Diagnosis and Recommendation Integrated System (DRIS). DRIS-based analysis predicted the optimum values of available nutrients in soil as 0.70-0.92% organic carbon, 27.46- 41.96 kg/ha Olsen-P, 232.51-303.11 kg/ha NH4OAc-K, 13.13-25.80 mg/kg DTPA- Fe, 0.95-1.18 mg/kg DTPA-Zn, 18.13-29.22 mg/kg DTPA-Mn and 1.12- 2.13 mg/kg DTPA-Cu in relation to fruit yield of 21.23-39.15 tonnes/ha in Sathgudi sweet orange. These indices identified the low levels of organic carbon (41% orchards), Olsen-P (45% orchards) and DTPA-Zn (32% orchards). While optimum levels of K, Fe, Cu, and Mn were observed in sweet orange growing orchards of Andhra Pradesh. The new DRIS norms for yield showed that the yield level should be considered as ‘low’ when it is less than 21.22 tonnes/ha.